(untitled) (Journal of Academic Research, 2021)
This study was conducted at Misurata City in Libya. Gel of linseed is primary a mixture of polysacharies which acid-catalyzed hydrolysis yield rhamonose fucose arabinose, xylose, glactose, galacturonic acide, and glucose. It used as an emulsifying agent for chocolate milk and functionally resembles arbic gum. In this study gel of linseed isolated from locally, Linseeds by hot water extract. Antimitotic action potential of extracted gel investigated using Allium cepa bioassay. Different concentration of gel (2.5%, 5%) were tested at different periods (2, 4, 6hours) on active growing root tip cells .Changes in the rate of cell division (mitotic index) was recorded. The result showed a significant decrease in mitotic index in treated cells in comparison with control. The result showed also that gel of linseed has more mitodepressant action than whole seed extract. IR of the extracted gel and whole seed extract were similar in band number and peaks. The data suggest that mitodepressnt effect of Linseed gel on rate of cell division may result of biologically active functional group of chemicals indicated by absorption spectra properties.